Analisis Pengaruh Kecerdasan Intelektual, Kecerdasan Spiritual, Dan Perilaku Belajar Terhadap Tingkat Pemahaman Akuntansi - Diningsih, Novelya A; Waromi, Juliana; Bleskadit, Novalia Herlina (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Cenderawasih, 2023)
This study aims to examine the influence of Intellectual Intelligence, Spiritual Intelligence, and Learning Behavior on the Level of Understanding of Accounting for Accounting Students of Cenderawasih University Jayapura. The study sample used purposive sampling method. The sample was 120 students. The approach used in research is a quantitative approach. The analysis tool used is a multiple linear regression analysis method using the help of SPSS software. The results of this study show that Intellectual Intelligence, Spiritual Intelligence, and Learning Behavior affect the Level of Understanding of Accounting of Cenderawasih University Students. For future research, it is expected that research can be carried out with more expanded sampling, and further research can replace independent variables to be wider and can also add other variable models. The object in this study only focuses on students of Cenderawasih University Jayapura, so the results of the study cannot be generalized to a wider sample. In addition, the independent variables used in this study are only three, namely intellectual intelligence, spiritual intelligence and learning behavior, so there are still other variables that are not studied that might affect the level of understanding of student accounting.